PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTA DI KALIMATAN BARAT - Melati Pramudita Lestari; Merry Triani; Yohanes Adi Nugroho; Fiorintari Fiorintari (Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the influence of local government characteristics on the financial performance of district/city governments in West Kalimantan Province. The population with this study is the district/city government in West Kalimantan Province which has 2 (two) cities and 12 (twelve) districts. Information on the realization of funds that can be observed is in 2017-2021 or for five years, finally the total population in this study is 70. The technique of determining the sample with this study is saturated sampling. Therefore, the joint sample of this study is all populations as many as 70 reports of fund realization in districts/cities in West Kalimantan Province. This study data was collected together with documentation methods and literature studies which were then processed with multiple linear regression analysis tests with the help of SPSS 25. The results of the study convey that the level of regional wealth and capital expenditure has a constructive impact relevant to the financial performance of local governments, depreciation capacity in the central government has a negative impact relevant to the financial performance of local governments, but regional status does not have an impact on the financial performance of local governments. Meanwhile, the characteristics of local governments simultaneously affect the financial performance of local governments.